Building Virtual SMEs: Ghanaian Firm Level Perspective - Awiagah Raphael (Graduate School of International Studies Ajou University, 2014)
E-commerce today is increasingly widening the concept of business from a simple transactional approach to a more complex and wider concept of inter-firm co-operation. Amidst globalization of markets, growing interpenetration and increased interdependence of economies, e-commerce adoption by organisations still remains a complex, elusive, yet extremely vital phenomenon and very little is known about its determinants. This study therefore aims at identifying the major determining factors that drive e-commerce adoption by Ghanaian SMEs and essentially develop practical implication for required action. The research integrated technological, organizational and environmental determinisms with social constructivism to build a practical framework for understanding adoption behaviour of SMEs in Ghana. Questionnaires were distributed to SME operators in Ghana with the aid of the Ministry of Trade and Industry. The data was analyzed based on a sample of one hundred and fifty-four out of two hundred questionnaires distributed. The study adopted the purposive sampling technique to gather the needed data for the analysis, but the probability of each of the respondents was not premeditated. In exception of the demographic and firm physiognomies, all the variables in the study were measured with numerical interval scales. With the aid of a seven point Likert scale, each construct was measured with multi-item scales. The variables included relative advantage, perceived credibility, management support, CEO self-efficacy, government support, enabling conditions, mimetic pressure, perceived behavior control, subjective norm, attitude and intention towards usage. Structural Equations Modeling (SEM) with the aid of smartpls was employed for the analysis, and twelve out of seventeen hypotheses were confirmed. Government support was seen to have the greatest direct impact on intentions to use e-commerce. Managerial support and presence of enabling and regulatory conditions were also seen to play a vital role in SME e-commerce adoption. Furthermore, the results also showed that Ghanaian SMEs have the tendency to imitate successful first-movers to avoid the risks attendant with the technology.
학위논문(석사)--아주대학교 Graduate School of International Studies :국제경영학과,2014. 8